Formulation of a Predictive Model for Flash Temperature in Single Asperity Contact between TC4 Titanium and Q235 Steel (International Journal of Food and Nutritional Sciences, 2022)
The primary potential ignition source for explosive atmospheres in low-speed metal friction is the friction-induced hot surfaces. Interestingly, the friction flash temperature tends to surpass the bulk temperature under identical conditions. Consequently, understanding whether it is the bulk temperature of the hot surface or the flash temperature of the asperity contact that first reaches the ignition temperature of the combustible gas becomes a pertinent area of investigation. This study addresses this concern by establishing a friction model, delving into the flash temperature of the asperities' contact between TC4 titanium alloy and Q235 steel under low-speed and low-load friction conditions. Leveraging the Hertz contact theory, the contact process of a single pair of asperities and the methodology for calculating the maximum flash temperature are analyzed. Two assumptions are considered in calculating the maximum flash temperature, and through regression analysis, a mathematical model for the flash temperature concerning load and relative velocity is derived. The study then computes the maximum bulk temperature and flash temperature under identical conditions, aiming to discern the true effective ignition source of gas under low-speed and low-load friction conditions.